“Fake News” or Real Science? Critical Thinking to Assess Information on COVID-19 - Puig, Blanca; Blanco-Anaya, Paloma; Pérez-Maceira, Jorge J. (Frontiers in Education, 2021)
Few people question the important role of critical thinking in students becoming active citizens; however, the way science is taught in schools continues to be more oriented toward “what to think” rather than “how to think.” Researchers understand critical thinking as a tool and a higher-order thinking skill necessary for being an active citizen when dealing with socio-scientific information and making decisions that affect human life, which the pandemic of COVID-19 provides many opportunities for. The outbreak of COVID-19 has been accompanied by what the World Health Organization (WHO) has described as a “massive infodemic.” Fake news covering all aspects of the pandemic spread rapidly through social media, creating confusion and disinformation. This paper reports on an empirical study carried out during the lockdown in Spain (March–May 2020) with a group of secondary students (N = 20) engaged in diverse online activities that required them to practice critical thinking and argumentation for dealing with coronavirus information and disinformation. The main goal is to examine students’ competence at engaging in argumentation as critical assessment in this context. Discourse analysis allows for the exploration of the arguments and criteria applied by students to assess COVID-19 news headlines. The results show that participants were capable of identifying true and false headlines and assessing the credibility of headlines by appealing to different criteria, although most arguments were coded as needing only a basic epistemic level of assessment, and only a few appealed to the criterion of scientific procedure when assessing the headlines.